Accelerated decomposition of Bi2S3 nanorods in water under an electron beam: a liquid phase transmission electron microscopy study. (15th February 2021) - Kim, Su Yeon; Kim, Ji Hyeon; Jeong, Taehyeon; Kim, Kyung Bin; Kim, Hyung Joong; Nam, Ki Min; Ahn, Sang Jung; Kwon, Ji Hwan; Kim, Young Heon
Abstract: Evaluating the stability of semiconductor photocatalysts is critical in the development of efficient catalysts. The morphological and microstructural behaviors of nanorod-shaped Bi2 S3 semiconductors in aqueous solution were studied using a liquid cell transmission electron microscopy (TEM) technique. The rapid decomposition of Bi2 S3 in water was observed under electron beam irradiation during TEM. Rounded bright spots due to a reduction in thickness were observed on the Bi2 S3 nanorods at the initial stage of the decomposition, and rounded dark particles appeared outside of the nanorods in the solution, continuing the decomposition. This was confirmed by analyzing the atomic structure of the newly formed small particles, which consisted of an orthorhombic Bi2 S3 phase. The stability-related decomposition of the Bi2 S3 nanorods was demonstrated by considering the reduction and oxidation potentials of Bi2 S3 in an aqueous solution. The effect of water radiolysis by the incident electron during TEM observations on the decomposition process was also determined by considering the time-dependent concentration behavior of the chemical species. Our study therefore reflects a novel route to evaluate the stabilities of semiconductor photocatalysts, which could ultimately solve a range of energy and environmental pollution problems.